Key personal insights and changing needs of osteoarthritis patients: an international quantitative survey analysis - Szekanecz, Zoltan; Osadcii-Zaiat, Diana; Bajkó, András; Minda, Hajnalka; Szerencsés, Dóra (Reumatologia, 2024)
Osteoarthritis (OA) presents significant challenges, imposing limitations on patients' daily activities. Factors such as restricted mobility, sedentary lifestyles, social isolation, and weight gain can exacerbate the difficulties faced by these individuals. Our study aimed to identify the needs and personal challenges faced by individuals with OA, and the impact of the COVID-19 pandemic. The research included a quantitative survey and a workshop involving a Scientific Leader Team. The quantitative survey was conducted among 400 patients in Bulgaria, Romania, Serbia, and Kazakhstan. All enrolled participants had experienced chronic musculoskeletal pain due to OA for at least three years and had received treatment with topical or oral medications. The cross-country workshop, conducted via Zoom, brought together prominent rheumatologists to discuss the survey results and explore patient support opportunities with healthcare providers. Over 60% of respondents reported that poor locomotor function adversely affected their daily activities. More than 50% stated that they had delayed treatment due to concerns about potential side effects, while over half expressed a desire for rapid pain relief. Approximately 30% of patients reported an increase in musculoskeletal complaints following the onset of the COVID-19 pandemic. The proportion of online consultations rose significantly, increasing from 5% before the pandemic to 12% during it, before stabilizing at 9% in the post-pandemic period. Patients with OA face considerable limitations in their daily lives, with a strong preference for immediate pain relief. Concerns about side effects lead many to postpone treatment. Over-the-counter anti-inflammatory creams and prescription oral anti-inflammatory drugs are the most used therapies. The pandemic negatively affected OA symptoms. Furthermore, the use of online channels for OA patient care increased during the COVID-19 pandemic.